Controversies in the treatment of immune thrombocytopenia. Issue 5 (September 2016) - Cuker, Adam; Cines, Douglas B.; Neunert, Cindy E.
Abstract : Purpose of review: We address three current controversies in management of immune thrombocytopenia (ITP): Should asymptomatic children with newly diagnosed ITP and severe thrombocytopenia be treated? Does intensification of up-front therapy in adults with newly diagnosed ITP impact long-term outcomes? Is splenectomy still the second-line treatment of choice in adults with chronic ITP? Recent findings: Severe bleeding is rare in children with ITP. There is little evidence that the platelet count predicts or that treatment prevents severe bleeding in this population. Intensified treatment with high-dose dexamethasone and rituximab in adults with newly diagnosed ITP is associated with improved platelet responses at 6 and 12 months but greater toxicity compared with standard therapy. Rituximab and thrombopoietin receptor agonists have emerged as suitable alternatives to splenectomy for second-line management of adults with chronic ITP. Summary: We generally observe children with newly diagnosed ITP and mild or no bleeding symptoms, irrespective of platelet count. We do not routinely use intensified up-front therapy in adults with newly diagnosed ITP. We discuss the advantages and disadvantages of splenectomy, rituximab, and thrombopoietin receptor agonists with our patients and make a joint decision that takes into consideration age, comorbidities, lifestyle, values, preferences, and financial considerations.